2021
DOI: 10.4103/jomfp.jomfp_454_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunohistochemical expression of epithelial–mesenchymal transition markers E-cadherin, Twist and Snail in oral submucous fibrosis and their possible association with malignant transformation

Abstract: Background: Oral submucous fibrosis (OSMF) is a chronic, potentially malignant condition of the oral mucosa, predominantly seen in people of Asian descent. The reported malignant transformation rate of OSMF is 7%–13%. In the context of the understanding progression of OSMF, the study of prime molecular expressions is essential. Various markers have received more attention, one of them is E-cadherin. Various factors which promote epithelial–mesenchymal transition (EMT) and inhibit E-Cadherin includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The most frequent mechanism by which ZEB 1induces EMT related fibrosis is by the activation of TGF-beta pathway. 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent mechanism by which ZEB 1induces EMT related fibrosis is by the activation of TGF-beta pathway. 29 …”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 expression in the stroma is similar to that found in immune cells and/or a subpopulation of fibroblasts. 29 The presence of ZEB1 in these stromal cells could indicate that it has an impact on the tumor microenvironment. It helps to create the tumor microenvironment by controlling the amounts of inflammatory cytokines like IL-6/8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 high power fields (40X), several positive cells were counted in the epithelium and connective tissue (connective tissue cells like fibroblasts and inflammatory cells), and the % positivity was computed. Counting was done on a computer display using the software ProgRes CapturePro v2.8.8 [19][20][21]. Briefly, CA 1, HSP 70 and 14-3-3ε expression was assessed semi-quantitatively by evaluating the percentage of epithelial and CT cells, 20% or more, expressing the respective proteins considered positive.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…E‑cadherin, Twist 1, and Snail 1 have been evaluated immunohistochemically in OSMF tissues, and their association with malignant transformation has been demonstrated, suggesting their role in EMT [ 47 ]. A previous study demonstrated an increase in the expression of Snail 1 and Twist with the concomitant loss of E-cadherin [ 48 ]. In addition to the direct effects of transcription factors on gene expression, there also occur some changes at the RNA level to regulate EMT progression such as alternative splicing of nascent RNAs into mRNAs that generate proteins with structural and functional differences in EMT.…”
Section: Reviewmentioning
confidence: 99%